2005
DOI: 10.1128/aem.71.1.594-596.2005
|View full text |Cite
|
Sign up to set email alerts
|

Novel Keratinase from Bacillus subtilis S14 Exhibiting Remarkable Dehairing Capabilities

Abstract: We report the isolation of a keratinolytic-producing Bacillus subtilis strain and the characterization of the exceptional dehairing properties of its subtilisin-like keratinase. This enzyme can be an alternative to sodium sulfide, the major pollutant from tanneries, and may completely replace it. Its unique nonactivity upon collagen enhances its industrial potential.Enzymatic dehairing in tanneries has been envisaged as an alternative to sulfides (4,6,9,22,23). Tanneries are constantly concerned about the obno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(86 citation statements)
references
References 17 publications
1
79
0
6
Order By: Relevance
“…Accompanied by feather degradation and keratinase production, the pH value of the culture increased to about 8.5. B. subtilis strains had been widely utilized for enzyme production, including the keratinases (Lal et al, 1999;Suh and Lee, 2001;Kim et al, 2001;Macedo et al, 2005). Other Bacillus species including B. licheniformis, B. pumilis, B. cereus, B. halodurans and B. pseudofirmus (Williams et al, 1990;Takami et al, 1999;Rozs et al, 2001;Kim et al, 2001;Gessesse et al, 2003;El-Refai et al, 2005) had also been reported for their keratinolytic activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accompanied by feather degradation and keratinase production, the pH value of the culture increased to about 8.5. B. subtilis strains had been widely utilized for enzyme production, including the keratinases (Lal et al, 1999;Suh and Lee, 2001;Kim et al, 2001;Macedo et al, 2005). Other Bacillus species including B. licheniformis, B. pumilis, B. cereus, B. halodurans and B. pseudofirmus (Williams et al, 1990;Takami et al, 1999;Rozs et al, 2001;Kim et al, 2001;Gessesse et al, 2003;El-Refai et al, 2005) had also been reported for their keratinolytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Among these strains, B. subtilis KD-N2 degraded feathers more quickly than any other reported until now, except for B. licheniformis RG1, which degraded feathers completely in 24 h (Ramnani and Gupta, 2004). Among the keratinases reported, only two of them had been purified (Suh and Lee, 2001;Macedo et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a positive control, collagen was incubated with collagenase from Clostridium histolyticum. Samples were collected at 0 and 24 h of incubation and analyzed on SDS PAGE [11].…”
Section: Analysis Of Collagenase Activitymentioning
confidence: 99%
“…Enzymes can be applied in different steps of the process, such as in soaking, liming, unhairing, bating, dyeing, and degreasing, as well as for effluent treatment, both solid and liquid (Kanth et al, 2009;Kanth et al, 2008;Macedo et al, 2005;Dayanandan et al, 2003;Lutckmeier et al, 2008;Kumar et al, 2008). Despite being consolidated in other industrial applications, the use of enzymes in the leather industry needs more research to be effectively used in large scale operations and at competitive costs.…”
Section: Introductionmentioning
confidence: 99%